2020
DOI: 10.3390/cells9051068
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone Induces HMGB1 Release in Primary Cultured Rat Cortical Astrocytes: Involvement of Pannexin-1 and P2X7 Receptor-Dependent Mechanisms

Abstract: A major risk factor for major depressive disorder (MDD) is stress. Stress leads to the release of high-mobility group box-1 (HMGB1), which in turn leads to neuroinflammation, a potential pathophysiological basis of MDD. The mechanism underlying stress-induced HMGB1 release is not known, but stress-associated glucocorticoids could be involved. To test this, rat primary cultured cortical astrocytes, the most abundant cell type in the central nervous system (CNS), were treated with corticosterone and HMGB1 releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 66 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…HMGB1 has been implicated in the stress-induced sensitization of innate immune cells and subsequent neuroinflammation ( Zhang et al, 2019 ). Also, it has been suggested that, under stress, GC may induce HMGB1 release ( Frank et al, 2015 ; Hisaoka-Nakashima et al, 2020 ).…”
Section: Immune System and Inflammationmentioning
confidence: 99%
“…HMGB1 has been implicated in the stress-induced sensitization of innate immune cells and subsequent neuroinflammation ( Zhang et al, 2019 ). Also, it has been suggested that, under stress, GC may induce HMGB1 release ( Frank et al, 2015 ; Hisaoka-Nakashima et al, 2020 ).…”
Section: Immune System and Inflammationmentioning
confidence: 99%
“…After drug treatment, media were collected and concentrated with trichloroacetic acid (catalog # 203‐04952; FUJIFILM Wako Pure Chemical Corporation, ). Concentrated media sample or cells were lysed with radio immunoprecipitation assay buffer (RIPA buffer) with inhibitors (100 mM Tris–HCl, pH 7.4, 150 mM NaCl, 1 mM EDTA, 1% Triton X‐100, 1% sodium deoxycholate, 0.1% sodium dodecyl sulfate (SDS), 20 µg/ml aprotinin, 20 µg/ml leupeptin, 1 mM phenylmethylsulfonyl fluoride, and phosphatase inhibitor cocktail (Nacalai Tesque, )) as described previously (Hisaoka‐Nakashima et al., 2020). Equal amounts of protein were separated by 12% SDS–polyacrylamide gel electrophoresis and blotted onto PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%
“…Immunocytochemistry of primary cultured rat cortical astrocytes was performed as described previously (Hisaoka‐Nakashima et al., 2020). Astrocytes were treated with LPA for 3 hr, and after washing, cells were fixed in 4% paraformaldehyde in PBS for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, chronic activation causes astrocytes to produce high levels of chemokines (Gimsa et al, 2013). Furthermore, hippocampal astrocytes mediate the depressive behavior induced by chronic stress (Hisaoka-Nakashima et al, 2020;Du Preez et al, 2021). Taken together, these findings indicate that dynamic changes in glia and their interactions contribute to the inflammatory processes involved in depression.…”
Section: Introductionmentioning
confidence: 92%